2018
DOI: 10.1002/eqe.3064
|View full text |Cite
|
Sign up to set email alerts
|

Effects of variation in loading protocol on the strength and deformation capacity of ductile reinforced concrete beams

Abstract: Summary Understanding the impact of prior earthquake damage on residual capacity is important for postearthquake damage assessment of buildings; however, interpretation of such impact is challenging when based on tests using traditional reversed‐cyclic loading protocols. A new loading protocol, consisting of a dynamic earthquake displacement history followed by quasi‐static reversed‐cyclic loading to failure, is presented as an alternative to traditional simulated seismic loading protocols. Data are analyzed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…1(b)], the expected loading cycles may not differ that much from those of a standard symmetric-cyclic loading protocol. Similar conclusions hold true for reinforced concrete members (Marder et al 2018).…”
Section: Loading Historysupporting
confidence: 78%
“…1(b)], the expected loading cycles may not differ that much from those of a standard symmetric-cyclic loading protocol. Similar conclusions hold true for reinforced concrete members (Marder et al 2018).…”
Section: Loading Historysupporting
confidence: 78%
“…Marder et al 14 . proposed a new “earthquake‐then‐cyclic protocol” as an alternative to traditional static loading protocols.…”
Section: Experimental Program and Test Resultsmentioning
confidence: 99%
“…Previous research [15] has shown that the number of loading cycles applied at or below 2% drift does not typically result in a reduced deformation capacity in ductile plastic hinges, based on tests of beams and columns with length (or height) to depth ratios of 2.2 to 5.7 (note that this study did not consider the effects of epoxy repair or strain ageing). This is further evidenced in Fig.…”
Section: Deformation Capacitymentioning
confidence: 94%
“…Analysis using the test results was not included in the data paper [12]. Information on the influence of loading protocol on beam response is included in Marder et al [15], while this paper is focused on epoxy repair of damaged plastic hinges. Three specimens (named LD-1-R, LD-2-R, and LD-2-LER-R, where "-R" denotes these as repaired) were repaired following initial damaging earthquake-displacement history loadings.…”
Section: Summary Of Relevant Experimental Tests Beam Tests By Marder mentioning
confidence: 99%
See 1 more Smart Citation